Negotiating with the Sacred Other: the Ancient Mechanisms of the Personal Vow Practice - Mirela Hrovatin (International Journal of Religious Tourism and Pilgrimage, 2020)
By questioning the anthropological definition of vows as instrumental prayers, which has been generally accepted since William Christian (1989) introduced it, the paper will discuss the notion of a vow as a personal prayer in the effort to expand it beyond the mere request for a miracle or fulfilment of a pilgrim’s or believer’s wish. The votive prayer is mentioned already in the Bible (Deut. 23) as a somewhat problematic way of communicating with God due to a promise it contains. Based on the Amir Mashiach’s (2014) interpretation of prayers as performative utterances in the Jewish tradition and Radoslav Katicic's (1990) linguistic research of the (pre)Slavic and Indo-European connection between legal and religious texts, the analysis will give an insight into the ancient mechanisms behind the practice of vowing, which has been continued as a part of personal piety in different religions. From this viewpoint, some of the reasons why vows have been inextricably related to sacred places and pilgrimage will be shown. The interpretation will in part lean on specific issues as opened by the researchers in the field of the Anthropology of Pilgrimage (among others, Badone, 1990; Coleman and Eade, 2004; Eade and Sallnow, 1991; Hermkens, Jansen and Nottermans, 2012), as well as on some of the historical changes of this practice (Andric, 1999; Cartledge, 1992; Hahn, 2007; Hyman, 2009). The examples used in the paper have been gathered from archival materials, and open and semi-structured interviews.